Answer:
The solution to the system of equations is y = -5 and x = -2.
Step-by-step explanation:
The question tells us to use substitution to solve the system. This means that the given value for x (in terms of y) should be substituted into the other equation. This is modeled below:
-4y - 5x = 30
-4y - 5(y+3) = 30
Next, we should use the distributive property to simplify the left side of the equation.
-4y -5y - 15 = 30
The next step is to combine like terms on the left side of the equation.
-9y - 15 = 30
Then, we can add 15 to both sides of the equation.
-9y = 45
Finally, we can divide both sides of the equation by -9.
y = -5
To find the value for x, we substitute in the value we just found for y into either of our original equations.
x = y + 3
x = -5 + 3
x = -2
Therefore, the correct answer is y = -5 and x = -2.
Hope this helps!
Answer:
Step-by-step explanation:
1 and 2 are vertical angles
Answer:
25
Step-by-step explanation:
We can use the Pythagorean theorem to fin x
a^2 + b^2 = c^2 where a and b are the legs and c is the hypotenuse
7^2 + 24^2 = x^2
49+ 576 = x^2
625 = x^2
Take the square root of each side
sqrt( 625) = sqrt(x^2)
25 = x
-- Kenny's weight is 6/7 of Melvin's weight.
-- Melvin's weight is 7/7 of Melvin's weight.
-- The ratio of Kenny's weight to Melvin's weight is (6/7) / (7/7) = 6/7 .